Corrigendum - Nakhaei, Jalal; Bitarafan, Mahdi; Arefi, Shahin Lale; Kapliński, Oleg (Journal of Civil Engineering and Management, 2016)
Corrigendum. Journal of Civil Engineering and Management, 22(7), p. 979.